Monolayer asphalt pavement. Western requirements in Polish realities - Koźlarek, Piotr (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
Polish road network is made up of 95% local roads. Their technical condition is much worse in comparison to motorways and national roads network. The lack of financial resources is one of the main reasons for this situation. That is why there is a continuous search for technologies, that allow for fast and cheap pavement repair or modernization. The monolayer asphalt pavement is such a solution offering in addition to cost effectiveness and shorter construction time, also an increased durability. Our western neighbors developed the technical regulations for this technology under the name "Asphalttragdeckschicht" which is marked as AC 16 TD. In direct translation "Asphalttragdeckschicht" means supporting wearing course / base layer. The monolayer asphalt pavement consists of a single layer with thickness between 5 to 10 cm made of HMA that links the functions of two layers – asphalt base course and asphalt wearing course. Thanks to this, the monolayer is resistant to environmental conditions and provides an adequate bearing capacity for a given traffic load. Insufficient funding and the impossibility to put the street out of operation were the bases for the investor’s decision to build a 220m section of road pavement using the monolayer pavement technology in Pruszków near Warsaw. This project gave the possibility to learn and gain an experience with a new western technology applied to Polish reality.